Correction: Comparative study of the extrinsic properties of poly(lactic acid)-based biocomposites filled with talc versus sustainable biocarbon. Issue 53 (14th October 2021) - Snowdon, Michael R.; Wu, Feng; Mohanty, Amar K.; Misra, Manjusri
Abstract : Correction for 'Comparative study of the extrinsic properties of poly(lactic acid)-based biocomposites filled with talc versus sustainable biocarbon' by Michael R. Snowdon et al., RSC Adv., 2019, 9, 6752–6761, DOI: ; 10.1039/C9RA00034H .